The Effect of Self-Efficacy and Knowledge on a Teacher’s Task Performance: A Case Study on Public Junior High School Teachers in South Bengkulu - Dona, Geistika Anugra; Pareke, Fahrudin JS (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aimed to determine how self-efficacy affects teacher task performance in SMP Negeri Bengkulu Selatan and how knowledge affects task performance. The quality of an agency can be seen from the task performance of its employees. Task performance can be improved by various aspects, such as fulfilling desires, work needs, individual and job compatibility, and formal and informal relationships with colleagues. The SmartPLS4 application was used for the SEM analysis method in this study. The sample was 110 teachers from all public junior high schools in South Bengkulu. The test results show that the self-efficacy variable has a positive and significant influence on the task performance of each teacher. In contrast, the knowledge variable does not significantly influence a teacher's task performance. The results showed a t-value of 5.387 > 1.96 and a p-value of 0.000 < 0.050, thus indicating that the self-efficacy variable significantly positively affects task performance. The study results show that the t-value of 1.206 < 1.96 and the p-value of 0.228 < 0.50 shows that the knowledge variable does not positively affect the task performance variable. This research aims to inspire teachers by considering that self-efficacy and knowledge can affect task performance individually and institutionally.